Effects of Interval Training on Visceral Adipose Tissue in Centrally Obese 70‐Year‐Old Individuals: A Randomized Controlled Trial. Issue 8 (23rd April 2019) - Ballin, Marcel; Lundberg, Emmy; Sörlén, Niklas; Nordström, Peter; Hult, Andreas; Nordström, Anna
Abstract : OBJECTIVE: To investigate the effects of 10 weeks of progressive vigorous‐intensity interval training as a single intervention on body composition among 70‐year‐old individuals with central obesity. DESIGN: Randomized controlled trial (ClinicalTrials.gov registration No. NCT03450655). SETTING: Community‐dwelling 70‐year‐old men and women living in the Umeå municipality in Sweden. PARTICIPANTS: Seventy‐seven 70‐year‐old men and women with central obesity (greater than 1 kg visceral adipose tissue [VAT] for women and greater than 2 kg VAT for men). INTERVENTION: Participants allocated to the intervention group were offered a 10‐week progressive concurrent exercise program performed three times per week. All participants in both groups had received tailored lifestyle recommendations focused on diet and physical activity at one occasion within 12 months prior to trial initiation. MEASUREMENTS: The primary outcome was changes in VAT, and secondary outcomes included changes in total fat mass (FM), total lean body mass (LBM), and body mass index. RESULTS: Comparing the groups, there were no significant differences in decrease of VAT mass ( P = .10), although the intervention group significantly decreased FM by 716 g ( P = .01) and gained LBM by 508 g ( P = .03), compared to the control group. Furthermore, the effects of the training were significantly greater in the male subcohort ( P < .05 for interaction), with positive effects also on VAT and FM, where men in the intervention group decreased VAT by 175 g ( P < .05) and FM by 1364 g ( P = .004), compared to the male controls. CONCLUSIONS: The present trial demonstrates that 10 weeks of progressive vigorous interval training is sufficient to significantly decrease FM in older adults with central obesity, with positive effects also on LBM. J Am Geriatr Soc 67:1625–1631, 2019